EFEKTIVITAS MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH SISWA DALAM MATA PELAJARAN EKONOMI KELAS X DI SMAN 1 TAMBANG - Aini Wilanda; R.M Riadi; Hardisem Syabrus (STKIP Subang, 2026)
This study aimed to analyze the effectiveness of the Problem Based Learning (PBL) model in improving the economic problem-solving skills of tenth-grade students at SMAN 1 Tambang. This study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of class X-1 as the experimental group (34 students) and class X-2 as the control group (32 students). The results showed that the average posttest score of the experimental class reached 79.18, significantly higher than that of the control class, which was 50.53. The N-Gain test indicated an effectiveness level of 55.21% (moderate category) in the experimental class, while the control class obtained -15.21% (ineffective category). Statistical analysis using the Mann-Whitney U test produced a significance value of 0.000 (< 0.05). The study concludes that the PBL model is significantly effective in improving students' problem-solving skills compared to conventional learning methods.